The Correlation Between Students’ Vocabulary Mastery and Speaking Mastery - Anry Ani; Yusni Sinaga (English Education : English Journal for Teaching and Learning, 2021)
The purpose of the research was to know the correlation between vocabulary mastery and speaking mastery at grade VIII students of SMP N 5 Padangsidimpuan. Type of this research was quantitative research with a correlational method. Based on calculation of the data, the researcher found that the score of rxy was more than rtable 0.737 0,423. It means the result showed that there was a significant correlation between two variables in the good category.